в. х + 4 = х + 2 х-х=2-4 0х=-2 уравнение не имеет решений, так как слева всегда 0, справа -2 0≠-2 г. 2х - 6 = 3х 2х-3х=6 -х=6 х=-6 д. 5х = 6х 5х-6х=0 -х=0 х=0 е. 2х + 5 - 7х + 2 = 3 2х-7х=3-5-2 -5х=-4 х=4/5 х=0,8 ж. 3х -5 =-2х + 7 + 5х - 12 3х+2х-5х=7-12+5 0х=0 х-любое число При любом х∈(-∞;+∞) слева 0 и справа 0, 0=0 з. х - 1 + 3х - 5 = (х-5)-(х-3)+(х+1) х-1+3х-5=х-5-х+3+х+1 х+3х-х+х-х=-5+3+1+1+5 3х=5 х=5/3 х=1 целая 2/3
х-х=2-4
0х=-2
уравнение не имеет решений, так как слева всегда 0, справа -2
0≠-2
г. 2х - 6 = 3х
2х-3х=6
-х=6
х=-6
д. 5х = 6х
5х-6х=0
-х=0
х=0
е. 2х + 5 - 7х + 2 = 3
2х-7х=3-5-2
-5х=-4
х=4/5
х=0,8
ж. 3х -5 =-2х + 7 + 5х - 12
3х+2х-5х=7-12+5
0х=0
х-любое число
При любом х∈(-∞;+∞)
слева 0 и справа 0, 0=0
з. х - 1 + 3х - 5 = (х-5)-(х-3)+(х+1)
х-1+3х-5=х-5-х+3+х+1
х+3х-х+х-х=-5+3+1+1+5
3х=5
х=5/3
х=1 целая 2/3